Penyandi Persepsi Isyarat Audio Berdasar pada Model Modulasi Frekuensi (FM) - Bondhan Winduratna (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Data compression or source coding has been playing an important role in many areas in daily life. There are several audio encoders available with various methods. Each audio encoder works at a certain range bitrate depending on the signal model used and the method implemented. Based on literature reviews it is to know that there are only a view of audio encoder working at bit rate below 16 kbit/s, especially for music signals.The togetherness in having harmonically components between the audio signals and frequency modulated signals is the basic idea of proposing the perceptual encoder based on FM signal model. In estimating and extracting FM parameters, the psychoacoustic model is used to exploit the perceptual nature of humans ears. The errors of FM modeling is distributed below the masking curve of psychoacoustic model. The developed encoder allows sending music signals on the GSM channel.The developed encoder has four cascaded main processes, namely sinusoid components extraction, harmonic components separation, FM parameters estimation, and FM parameter encoding. The simulation results show the proposed method is successful to encode some audio signal types.